PENGARUH MOTIVASI, PERSEPSI BIAYA, DAN LAMA PENDIDIKAN TERHADAP MINAT MAHASISWA UNTUK MELANJUTKAN PROGRAM PASCASARJANA MAGISTER AKUNTANSI (Studi Kasus Pada Mahasiswa Program Akuntansi Universitas Islam Malang) - Rayi Mifta Pradifta; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims: to analyze the influence of motivation, perception of costs and length of education against the interest of students to continue the Post-Master of Accounting Program. The research method uses quantitative research using population and the particular sample. The method used in collecting data in this study a questionnaire, observation, and library research (documentation). This research was conducted by taking research in the Faculty of Economics and Business Accounting Studies Program University of Islam Malang and use the questionnaire as a basic information gathering. The population of this research is all students S1 8th semester Faculty of Economics and Business Accounting Studies Program University Islam Malang. with a sample of 68 students. The sampling method in this research is to use the easy way (convenience sampling) is to take samples in accordance with the provisions and requirements of a specific sample of the population that is most accessible and available. The analytical tool used: multiple linear regression, t-test, F and coefficient of determination (R2 ). The results of data analysis can be obtained as follows : Variable Motivation , Perceived Costs and Duration of Education has an influence on the student 's interest to continue the Post- Master of Accounting Program, evidenced by the significant of value < 0.05 means that a hypothetical received stating Motivation , Perceived Costs and Duration of Education have influence Student interest to proceed against the Post Master of Accounting Program.Keywords: Motivation, Perceived Costs And Old Education and Student Interests.